Incidence and Predictors of Tuberculosis among Adult PLWHA at Public Health Facilities of Hawassa City - Henok Bekele; Mesfin Kote; Aman Yesuf; Tadele Girum (International Journal of Public Health Science (IJPHS), 2017)
Tuberculosis (TB) is the most frequently diagnosed opportunistic infection (OI) and disease in people living with HIV/AIDS (PLWHA), world-wide. This study aimed at determining the incidence and predictors of tuberculosis among people living with HIV.A Six year retrospective follow up study was conducted among adult PLHIV. The Cox proportional hazards model was used to identify predictors.A total of 554 patients were followed and produced 1830.3 person year of observation. One hundred sixty one new TB cases occurred during the follow up period. The overall incidence density of TB was 8.79 per 100 person-year (PY). It was high (148.71/100 PY) in the first year of enrolment. The cumulative proportion of TB free survival was 79% and 67% at the end of first and sixth years, respectively. Not having formal education(AHR=2.68, 95%CI: 1.41, 5.11 ), base line WHO clinical stage IV (AHR = 3.22, 95% CI=1.91-5.41), CD4 count <50 cell/ul  (AHR=2.41, 95%CI=1.31, 4.42), Being bed redden (AHR= 2.89, 95%CI=1.72, 3.78), past TB history (AHR=1.65, 95% CI = 1.06,2.39), substance use (AHR=1.46, 95% CI=1.03,2.06) and being on pre ART (AHR=1.62, 95%CI:1.03-2.54 ) were independently predicted tuberculosis occurrence. Advanced WHO clinical stage, limited functional status, past TB history, addiction and low CD4 (<50cell/ul) count at enrollment were found to be the independent predictor of tuberculosis occurrence. Therefore early initiation of treatment and intensive follow up is important.